Living with systemic lupus erythematosus in 2024: Latin American experience based on a patient survey (2025)
Objective To assess the burden of systemic lupus erythematosus (SLE) from the perspective of patients in Latin America (LATAM) in 2024. Methods During May 2024, as part of International SLE Awareness Day, the Grupo Latinoamericano de Estudio del Lupus (GLADEL) disseminated an anonymous, bilingual (Spanish/Portuguese) online survey to patients with SLE. The survey, developed by Lupus Europe, was distributed through physicians and patient associations across LATAM and explored sociodemographic characteristics, disease features, treatments, and the impact on daily life. Results A total of 1991 responses from 21 Latin American countries were analyzed (Argentina, Brazil, the Dominican Republic, Chile, and Peru contributing the highest numbers). Most respondents were women (95.2%), with a mean age of 38.6 years (SD 11.6). Overall, 52.1% were married or partnered, 34.0% had completed secondary/vocational education, and 38.8% were employed. Regarding ethnicity, 25.5% identified as Caucasian and 34.4% as Mestizo. A prior alternative diagnosis was reported by 59.7%, with a mean age at diagnosis of 28.8 years (SD 10.6) and a median delay of 1 year (IQR 0–2). The most frequently affected organs were joints (71.4%), skin (47.4%), and kidneys (37.5%). Emotional and sexual life were negatively affected in 43.2%, and 62.1% reported impacts on education or career. Anxiety and/or depression were reported by 60%. Antimalarials, corticosteroids, immunosuppressives, and biologics were used by 80.9%, 55.7%, 59.9%, and 11.1%, respectively. Notably, 67.7% perceived their disease as under control. Conclusion Understanding patient perspectives is essential to evaluate the burden of SLE, and incorporating patient-reported experiences into decision-making should be prioritized.